Parental Satisfaction towards Care Given at Neonatal Intensive Care Unit and Associated Factors in Comprehensive and Referral Hospitals of Southern Ethiopia - Eden Sileshi; Bedria Mohammed; Derese Eshetu; Aster Dure; Agegnehu Bante; Abera Mersha; Teketel Ermias Geltore (Journal of Pregnancy)
Background. Patient satisfaction is an important aspect of the quality of care in the inpatient setting. In neonatal intensive care units, parents’ satisfaction and their experiences are fundamental to assessing clinical practice and improving the quality of care delivered to infants. Hence then, it reduces infant mortality rates globally. In Ethiopia, few studies address the level of parental satisfaction towards care given at neonatal intensive care unit and no single study was done in the study area. Therefore, this study is aimed at assessing parental satisfaction towards care given at neonatal intensive care unit and associated factors in comprehensive and referral hospitals of southern Ethiopia. Methods. An institutional-based cross-sectional study was conducted among 401 parents who visited neonatal intensive care from March 28 to April 28, 2022. The data were assorted via a structured interviewer-administered questionnaire using ODK collect version and exported to SPSS window version 25 for further cleaning and analysis. Bivariate and multivariate logistic regressions were used to identify factors associated with parental satisfaction with care given at the neonatal intensive care unit. The adjusted odds ratio with 95% CI was used to show the strength of the association, and a P value < 0.05 was used to declare the cutoff point to determine the level of significance. Results. In this study, 63% (95% CI: 58%, 68%) of the parents were satisfied with the care given at the neonatal intensive care unit. Factors associated with parental satisfaction towards care given at neonatal intensive care unit were parents with no formal education (AOR: 0.15; 95% CI: 0.07-0.31), availability of necessary information using direction indicator (AOR: 3.14; 95% CI: 1.85-5.31), and availability of enough chairs in waiting area (AOR: 3.26; 95% CI: 1.81-5.87). Conclusion. Nearly two-thirds of the parents were satisfied with the care given at the neonatal intensive care unit. The availability of enough chairs in the waiting area and the creation of direction indicators are key issues to improve parental satisfaction towards their neonatal care.